Phonetic and phonological univerisals in reciprocal assimilations (Philology, 2026)
Reciprocal assimilation is a phonological process in which two adjacent segments, or the two components of a consonant with a secondary articulation, fuse together to form an intermediate segment which receives some features from the first and some others from the second. This paper investigates the phonological parameters of reciprocal assimilation in consonants and vowels by pointing out some typological tendencies observed in this phenomenon. These tendencies are related to articulatory, perceptual or aerodynamic parameters of the vocal tract and speech production to find a logical phonetic explanation for them.
Keywords: phonetics; phonology; reciprocal assimilation; language universals